Principles of Teaching Professionalism Ethics: A Conceptual Review - Gurumoorthy Poobalan; Roslee Talip; Junaidi Asman; Mazni Mustapha; Sukuneswari Kaliappan; Muhammad Din Sulaiman; Lindy Marcus; Amrah Mohamad; Rosna Padan (Global Scientific and Academic Research, 2023)
This concept paper discusses and purposes the principles of teaching ethics in Malaysia. Teachers' ethics play an important role in achieving educational transformation. Therefore, the teachers should apply ethics in teaching in line with the Malaysia Education Blueprint (2013- 2025). Researchers uncover 6 principles of teaching ethics in order to improve the quality of teaching professionalism. To find the information needed, the researcher used a library study. Based on Findings, the study reveal 6 principles as equality, openness, secrecy, loyalty, perseverance, and avoid conflicts of interest in enhancing the quality teaching professionalism. The findings of the study will fill the gaps of future literature review of principles of teaching ethics among school teachers.